Adjektiv-Attribute in German and Vietnamese: a Comparison - Nguyen Thi Kim Lien (Future Science)
In German, especially in written documents, complex noun phrases, including noun phrases using adjectives as determiners, are used a lot, which notably caused many difficulties to students of German. Therefore, this study has raised the following questions: Is there any similarity or difference in the structure of a noun phrase using adjectives as determiners? How do Vietnamese students translate noun phrases using adjectives as determiners from Vietnamese to German? To answer these questions, this study conducts research on learner data from the HANU-VIELKO data source, which includes tests and exams of students of the German Department. The purpose of this study is to investigate the similarities and differences in the structure of noun phrases using adjectives as determiners in the two languages and to examine how students translate these structures from Vietnamese to German. Based on the study results, some comments and suggestions for quality improvement of teaching and learning in the Translation classes will be given.